1989
DOI: 10.1136/bmj.298.6676.832-b
|View full text |Cite
|
Sign up to set email alerts
|

Emergency external fixators.

Abstract: it does contain records of day case hysterectomies and total hip replacements. We have passed Messrs Drife and Macafee's other observations on to the Office of Population Censuses and Surveys, who will no doubt appreciate their humour very much. After all, an error rate of about 1 in 1000 is far better than could have been expected in hospital discharge statistics and, though perhaps significant, is absolutely negligible-a distinction about which statisticians are obviously still failing to educate clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…110 In the prevention of colitis, COS can also replace HMOs to play a role in the function, COS can also effectively prevent experimental colitis in vivo . Chitosan significantly regulates IL-6 and TNF-a signaling pathways 111 in the gut Oral COS protects the integrity of the gut epithelial barrier through antioxidant and anti-apoptotic mechanisms, and previous studies have shown that COS prevents colitis by inhibiting NF-κB activation and preventing TNF-α and oxidative stress-induced apoptosis of IEC. 112 COS significantly improves the abundance of the beneficial gut microbiota, especially Bifidobacterium , which has the potential to be used in combination with HMOs to promote the metabolism of HMOs, and COS, as a probiotic, also plays a positive role in reducing inflammation and increasing the gut barrier.…”
Section: Functional Oligosaccharidesmentioning
confidence: 99%
“…110 In the prevention of colitis, COS can also replace HMOs to play a role in the function, COS can also effectively prevent experimental colitis in vivo . Chitosan significantly regulates IL-6 and TNF-a signaling pathways 111 in the gut Oral COS protects the integrity of the gut epithelial barrier through antioxidant and anti-apoptotic mechanisms, and previous studies have shown that COS prevents colitis by inhibiting NF-κB activation and preventing TNF-α and oxidative stress-induced apoptosis of IEC. 112 COS significantly improves the abundance of the beneficial gut microbiota, especially Bifidobacterium , which has the potential to be used in combination with HMOs to promote the metabolism of HMOs, and COS, as a probiotic, also plays a positive role in reducing inflammation and increasing the gut barrier.…”
Section: Functional Oligosaccharidesmentioning
confidence: 99%